Comparison between general, spinal, epidural, and combined spinal-epidural anesthesia for cesarean delivery: a network meta-analysis. (February 2019) - Kim, W.H.; Hur, M.; Park, S.-K.; Yoo, S.; Lim, T.; Yoon, H.K.; Kim, J.-T.; Bahk, J.-H.
Highlights: There are four different anesthetic techniques for cesarean delivery. Neuraxial anesthesia is considered superior to general anesthesia for fetal outcomes. Previous studies and meta-analyses reported mixed results. This network analysis shows advantages of neuraxial anesthesia for Apgar score. Abstract: Background: This study is a network meta-analysis to compare maternal and fetal outcomes associated with four different anesthetic techniques for cesarean delivery. Methods: An arm-based, random-effects frequentist network meta-analysis was performed. A random effect model was selected considering deviance information criteria. Randomized trials reporting the following outcomes were included: Apgar score at 1- or 5-min; umbilical arterial and venous pH; umbilical arterial pH <7.2; and neonatal score at 2–4 hours. Loop-specific heterogeneity was evaluated by risk of odds ratio and τ 2 . Quality of evidence was assessed using the GRADE approach. Results: Data from 46 randomized trials including 3689 women contributed to the study. There were significant differences in Apgar score ≤6 at 1 min between spinal versus general anesthesia (odds ratio 0.27, 95% confidence interval [CI] 0.13 to 0.55: moderate quality evidence) and Apgar scores at 1- and 5-min, favoring spinal anesthesia. Umbilical venous pH associated with epidural anesthesia was significantly higher than that with general anesthesia (mean difference 0.010, 95% CI 0.001 to 0.020: moderate quality evidence) or spinal anesthesia. Spinal anesthesia was ranked best for Apgar score ≤6 at 1-min (SUCRA=89.8), Apgar score at 1-min (SUCRA=80.4) and 5-min (SUCRA=90.5). Epidural anesthesia was ranked highest for umbilical venous pH (SUCRA=87.4) and neonatal score (SUCRA=79.3). Conclusions: Spinal and epidural anesthesia were ranked high regarding Apgar scores and epidural anesthesia was ranked high regarding umbilical venous pH, but the results were based on small heterogeneous studies with high or unclear risks of bias.